Peningkatan Hasil Belajar IPAS Menggunakan Model Problem Based Learning berbantuan Media Powerpoint Interaktif - Ratnasari, Dyah; Khusnul Fajriyah; Joko Sulianto; Chiara Prima Matroianni Arifin (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
Learning outcomes in Natural and Social Sciences (IPAS) for Grade III students at SDN Sawah Besar 01 were low, marked by students’ lack of enthusiasm, passive participation, and limited understanding of the material. These issues stemmed from teacher-centered learning approaches and minimal use of engaging interactive media. This study aims to improve students' learning outcomes through the implementation of the Problem Based Learning (PBL) model supported by interactive PowerPoint media. The research used a Classroom Action Research (CAR) design, conducted in two cycles consisting of planning, action, observation, and reflection phases. The research subjects were 29 third-grade students. Data collection techniques included learning outcome tests, observation of student activities, and documentation. The results showed a significant improvement in students' learning outcomes. The average score increased from 65.9 in the pre-cycle to 74.6 in the first cycle, and reached 85.6 in the second cycle. Additionally, the percentage of students achieving the Minimum Mastery Criteria (MMC) rose from 20.6% in the pre-cycle to 62.1% in the first cycle and 93.1% in the second cycle. These findings demonstrate that the PBL model, when supported by interactive PowerPoint media, is effective in enhancing students' understanding and performance in IPAS learning.